FINANCIAL CAPACITY OF TERRITORIAL COMMUNITIES IN WARTIME CONDITIONS - Сокровольська, Наталія; Горжовський, С.М.; Череп, М.Я. (SWorldJournal, 2025)
The financial capacity of territorial communities in Ukraine during the full-scale war is analyzed in this article. The impact of fiscal centralization on the ability of local self-government bodies to fulfill delegated responsibilities has been examined,